A Civil-Military Response to Hybrid Threats (Springer International Publishing, 2018)
This edited volume provides scholars and practitioners with an in-depth examination of the role of civil-military cooperation in addressing hybrid threats. As they combine the simultaneous employment of conventional and non-conventional tools and target not only military objectives but governments and societies at large, hybrid threats cannot be countered solely by military means, but require an equally inclusive response encompassing a wide range of military and civilian actors. This book, which combines the perspectives of academics, military officers, and officials from international and non-governmental organisations, resorts to different case studies to illustrate the importance of civil-military cooperation in enhancing the resilience of NATO members and partners against a wide range of societal destabilization strategies, thereby contributing to the formulation of a civil-military response to hybrid threats. .